Process for preparing flow battery diaphragm from modified SiO2

By hydrophobic modification of SiO2 nanoparticles and composited with Nafion resin, the problems of low mechanical strength and insufficient electrolyte barrier capacity in high temperature and high humidity environments are solved, and the efficient proton conductivity, mechanical strength of the separator is achieved. Improvement of electrolyte barrier performance.

CN119419307APending Publication Date: 2025-02-11山西国润储能科技有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411593847.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-08
Publication Date
2025-02-11

AI Technical Summary

Technical Problem

The existing flow battery separator materials have low mechanical strength and insufficient electrolyte barrier capacity in high temperature and high humidity environments, resulting in diaphragm deformation, failure and cross-contamination of electrolyte, reducing battery efficiency and life.

Method used

By hydrophobic modification of SiO2 nanoparticles with n-octyltriethoxysilane and composited with Nafion resin, the uniform dispersion and tightness of SiO2 nanoparticles in the Nafion matrix are ensured through ultrasonic treatment and the use of fluorocarbon surfactant. Combined.

Benefits of technology

It significantly improves the proton conductivity, mechanical strength and electrolyte barrier properties of the separator, ensures that excellent performance can be maintained in high temperature and high humidity environments, and extends the service life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119419307A_ABST
    Figure CN119419307A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of electrochemical energy storage materials, and discloses a process for preparing a flow battery diaphragm from modified SiO2, and the process comprises the following steps: S1, preparing a silane coupling agent hydrolysate, dissolving n-octyltriethoxysilane in a mixed solution of ethanol and deionized water, and stirring under an acidic condition to generate a silanol monomer; s2, dispersing the SiO2 nanoparticles in ethanol or toluene, and performing ultrasonic dispersion to form a uniform SiO2 suspension; and S3, dropwise adding the silanol monomer in the step S1 into the SiO2 suspension, carrying out stirring reaction, carrying out condensation reaction on the silanol and the surfaces of the SiO2 particles to form Si-O-Si bonds, and grafting the flexible chain polymer on the surfaces of the nano rigid SiO2 particles. The silicon dioxide nanoparticles are modified by n-octyltriethoxysilane, and the fluorocarbon surfactant is introduced, so that the dispersity, proton conductivity, mechanical strength and electrolyte barrier property of the composite diaphragm are improved, and the problems of nanoparticle aggregation and electrolyte permeation are solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of electrochemical energy storage materials, and in particular to a modified SiO 2 Process for preparing flow battery separators. Background Art

[0002] Liquid flow battery is a reversible electrochemical energy storage system. It is widely used in large-scale power storage systems due to its advantages such as efficient energy conversion, long life and high capacity. As one of the key components of liquid flow battery, the performance of the diaphragm largely determines the overall efficiency and life of the battery. The diaphragm needs to effectively block the positive and negative electrolytes while maintaining good proton conductivity to prevent cross contamination. However, existing diaphragm materials still face some performance bottlenecks, especially in terms of proton conductivity, electrolyte barrier properties, mechanical strength and other aspects. There are still challenges in improving performance.

[0003] Currently widely used diaphragm materials, such as Nafion resin, have good proton conductivity and chemical stability, but they show some shortcomings under certain application conditions, especially in high temperature and high humidity environments. First, the mechanical strength of the Nafion diaphragm is relatively low. Under high temperature, high humidity or long-term operation, the diaphragm may deform or fail. Secondly, the electrolyte barrier ability of the Nafion diaphragm is not strong enough, which makes it easy for the positive and negative electrolytes to cross-contaminate through the diaphragm, reducing the overall efficiency and service life of the battery.

[0004] In order to solve these problems, researchers have tried to enhance the mechanical properties and electrolyte barrier properties of the diaphragm by introducing inorganic fillers (such as silica, titanium dioxide, etc.) into the Nafion matrix. Inorganic nanoparticles have excellent physical and chemical properties, such as high mechanical strength and chemical corrosion resistance, and are therefore considered to be an ideal choice for improving the performance of diaphragms. However, silica (SiO 2 ) Nanoparticles tend to aggregate in the polymer matrix due to their high specific surface area and surface energy, resulting in uneven dispersion in Nafion and inability to fully exert their reinforcing effect. This agglomeration phenomenon not only weakens the reinforcing effect of the nanoparticles, but may also lead to a decrease in the conductivity and mechanical properties of the diaphragm.

[0005] In addition, the compatibility between existing inorganic fillers and polymer matrices such as Nafion is poor, and nanoparticles tend to aggregate on the surface or interface of the matrix and cannot be evenly dispersed into the polymer network. Therefore, improving the compatibility of inorganic nanoparticles with polymer matrices is a key technical challenge to improve the performance of diaphragms. Summary of the invention

[0006] In view of the shortcomings of the prior art, the present invention provides a modified SiO 2The process for preparing liquid flow battery separators solves the problems of uneven dispersion, poor compatibility and agglomeration of silica nanoparticles in the Nafion matrix.

[0007] To achieve the above objectives, the present invention is implemented through the following technical solutions: a modified SiO 2 The process for preparing a flow battery separator comprises the following steps:

[0008] S1, preparing a silane coupling agent hydrolyzate, dissolving n-octyltriethoxysilane in a mixed solution of ethanol and deionized water, and stirring under acidic conditions to generate a silanol monomer;

[0009] S2, SiO 2 The nanoparticles were dispersed in ethanol or toluene and dispersed by ultrasonic to form a uniform SiO 2 Suspension;

[0010] S3, add the silanol monomer in step S1 dropwise to SiO 2 The suspension is stirred to react with silanol and SiO 2 Condensation reaction occurs on the particle surface to form Si-O-Si bonds, and the flexible chain polymer is grafted onto the nano-rigid SiO 2 Particle surface;

[0011] S4, modified SiO 2 The particles were added to the Nafion resin solution and treated with ultrasound to make them uniformly dispersed;

[0012] S5, adding fluorocarbon surfactant, stirring evenly and casting into a film;

[0013] S6, preliminarily drying at 70°C-80°C, and then further drying at a high temperature of 120°C-140°C to prepare modified SiO 2 Composite flow battery membrane with Nafion.

[0014] Preferably, the step S1 specifically includes the following steps:

[0015] S1.1. Preparation of solvent and catalyst:

[0016] Ethanol and deionized water are mixed in a volume ratio of 90:10 to 98:2 as a dissolving agent;

[0017] Add 0.05M to 0.2M hydrochloric acid as a catalyst to the mixed solvent;

[0018] S1.2, addition of n-octyltriethoxysilane:

[0019] The addition amount of n-octyltriethoxysilane is SiO 22%-10% of the particle mass;

[0020] n-Octyltriethoxysilane is added dropwise to the solution at a rate of 1 mL / min-10 mL / min, and stirred at room temperature with a stirring speed of 100 rpm-300 rpm and a reaction time of 0.5-2 h.

[0021] Preferably, the step S2 specifically includes the following steps:

[0022] S2.1, SiO with a particle size of 10nm-30nm 2 1g-5g of nanoparticles are added to ethanol or toluene solution, and the solvent volume is 30mL-100mL;

[0023] S2.2, ultrasonically disperse the SiO2 by using an ultrasonic processor with a frequency of 20kHz-60kHz and a power of 200W-600W for 10min-60min to obtain uniformly dispersed SiO2 2 Suspension.

[0024] Preferably, in step S3, the stirring temperature is 40° C.-80° C., and the stirring time is 4 h-8 h.

[0025] Preferably, the step S4 specifically includes the following steps:

[0026] S4.1, preparation of Nafion resin solution: Nafion resin and N,N-dimethylformamide are mixed in a mass ratio of 1:5-1:10, and stirred at 180°C-240°C for 2h-6h until the Nafion resin is completely dissolved;

[0027] S4.2, Modified SiO 2 Addition of nanoparticles: Modified SiO 2 The nanoparticles are added to the Nafion solution at a ratio of 1wt% to 3wt%;

[0028] S4.3. Ultrasonic treatment: Use an ultrasonic processor to treat the mixed solution prepared in step S4.2, with an ultrasonic frequency of 20kHz-60kHz, a power of 200W-500W, and a treatment time of 10min-60min.

[0029] Preferably, the step S5 specifically includes the following steps:

[0030] S5.1. Addition of fluorocarbon surfactant: The amount of fluorocarbon surfactant added is 0.5wt%-2wt% of the total mass of Nafion solution;

[0031] S5.2, stirring conditions: stirring at a temperature of 20°C-60°C for 1h-3h, and a stirring speed of 100rpm-400rpm;

[0032] S5.3, ultrasonic stirring: place the solution in an ultrasonic bath, the ultrasonic time is 10min-60min, and the ultrasonic frequency is 20kHz-40kHz;

[0033] S5.4. Film casting: Cast the composite solution evenly on a clean glass plate.

[0034] Preferably, in the step S6, the initial drying rate is 0.1°C / min-0.5°C / min, and the high temperature drying rate is 0.2°C / min-1°C / min, so as to control the porosity of the membrane to be 20%-40%.

[0035] Preferably, the SiO in step S3 2 The pH value of the suspension was controlled at 3-5.

[0036] Preferably, during the film forming process of step S5.4, the viscosity of the solution is adjusted to 100 cP-500 cP, and a layer-by-layer casting method is used to form a multi-layer composite diaphragm, wherein the thickness of each layer is controlled to be 20 μm-80 μm.

[0037] Preferably, the SiO modified in step S4 2 The contact angle of the nanoparticles after surface modification is controlled to be greater than 90°.

[0038] The present invention provides a modified SiO 2 The process for preparing a liquid flow battery separator has the following beneficial effects:

[0039] 1. The present invention solves the problem of SiO by using n-octyltriethoxysilane to hydrophobically modify silicon dioxide nanoparticles. 2 The agglomeration problem of nanoparticles due to their high specific surface area and high surface energy is a problem that the modified SiO 2 Si-O-Si bonds are formed on the surface of the nanoparticles, which significantly enhances their dispersibility in organic solvents. At the same time, the compatibility with Nafion resin is greatly improved, ensuring the uniform distribution of the particles in the Nafion matrix.

[0040] 2. The modified SiO 2The dispersion of nanoparticles in Nafion resin not only provides more microporous structures for proton conduction, but also ensures the effective bonding between the particles and the resin matrix by regulating the contact angle of the modified particle surface. Combined with the use of fluorocarbon surfactants, the ion exchange capacity and ion conductivity of the membrane are further improved. The final composite membrane can still maintain excellent ion conductivity in high temperature and high humidity environments, while also having excellent mechanical strength.

[0041] 3. The present invention significantly improves the barrier performance of the diaphragm to the electrolyte, reduces the permeability of the electrolyte, and reduces the cross-contamination problem of the membrane in the liquid flow battery by introducing fluorocarbon surfactants and controlling the preparation and drying processes of the membrane. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] Figure 1 It is a flow chart of the present invention. DETAILED DESCRIPTION

[0043] The technical solution of the present invention will be described clearly and completely below in conjunction with the accompanying drawings of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0044] Please see attached Figure 1 The embodiment of the present invention provides a modified SiO 2 The process for preparing a flow battery separator comprises the following steps:

[0045] S1, preparing a silane coupling agent hydrolyzate, dissolving n-octyltriethoxysilane in a mixed solution of ethanol and deionized water, and stirring under acidic conditions to generate a silanol monomer;

[0046] S2, SiO 2 The nanoparticles were dispersed in ethanol or toluene and dispersed by ultrasonic to form a uniform SiO 2 Suspension;

[0047] S3, add the silanol monomer in step S1 dropwise to SiO 2 The suspension is stirred to react with silanol and SiO 2 Condensation reaction occurs on the particle surface to form Si-O-Si bonds, and the flexible chain polymer is grafted onto the nano-rigid SiO 2 Particle surface;

[0048] S4, modified SiO 2 The particles were added to the Nafion resin solution and treated with ultrasound to make them uniformly dispersed;

[0049] S5, adding fluorocarbon surfactant, stirring evenly and casting into a film;

[0050] S6, preliminarily drying at 70°C-80°C, and then further drying at a high temperature of 120°C-140°C to prepare modified SiO 2 Composite flow battery membrane with Nafion.

[0051] The S1 step specifically includes the following steps:

[0052] S1.1. Preparation of solvent and catalyst:

[0053] Ethanol and deionized water are mixed in a volume ratio of 90:10 to 98:2 as a dissolving agent;

[0054] Add 0.05M to 0.2M hydrochloric acid as a catalyst to the mixed solvent;

[0055] S1.2, addition of n-octyltriethoxysilane:

[0056] The addition amount of n-octyltriethoxysilane is SiO 2 2%-10% of the particle mass;

[0057] n-Octyltriethoxysilane is added dropwise to the solution at a rate of 1 mL / min-10 mL / min, and stirred at room temperature with a stirring speed of 100 rpm-300 rpm and a reaction time of 0.5-2 h.

[0058] The S2 step specifically includes the following steps:

[0059] S2.1, SiO with a particle size of 10nm-30nm 2 1g-5g of nanoparticles are added to ethanol or toluene solution, and the solvent volume is 30mL-100mL;

[0060] S2.2, ultrasonically disperse the SiO2 by using an ultrasonic processor with a frequency of 20kHz-60kHz and a power of 200W-600W for 10min-60min to obtain uniformly dispersed SiO2 2 Suspension.

[0061] In step S3, the stirring temperature is 40°C-80°C, and the stirring time is 4h-8h.

[0062] The S4 step specifically includes the following steps:

[0063] S4.1, preparation of Nafion resin solution: Nafion resin and N,N-dimethylformamide are mixed in a mass ratio of 1:5-1:10, and stirred at 180°C-240°C for 2h-6h until the Nafion resin is completely dissolved;

[0064] S4.2, Modified SiO 2 Addition of nanoparticles: Modified SiO 2 The nanoparticles are added to the Nafion solution at a ratio of 1wt% to 3wt%;

[0065] S4.3. Ultrasonic treatment: Use an ultrasonic processor to treat the mixed solution prepared in step S4.2, with an ultrasonic frequency of 20kHz-60kHz, a power of 200W-500W, and a treatment time of 10min-60min.

[0066] Step S5 specifically includes the following steps:

[0067] S5.1. Addition of fluorocarbon surfactant: The amount of fluorocarbon surfactant added is 0.5wt%-2wt% of the total mass of Nafion solution;

[0068] S5.2, stirring conditions: stirring at a temperature of 20°C-60°C for 1h-3h, and a stirring speed of 100rpm-400rpm;

[0069] S5.3, ultrasonic stirring: place the solution in an ultrasonic bath, the ultrasonic time is 10min-60min, and the ultrasonic frequency is 20kHz-40kHz;

[0070] S5.4. Film casting: Cast the composite solution evenly on a clean glass plate.

[0071] In step S6, the initial drying rate is 0.1°C / min-0.5°C / min, and the high temperature drying rate is 0.2°C / min-1°C / min, so as to control the porosity of the membrane to be 20%-40%.

[0072] SiO in step S3 2 The pH value of the suspension was controlled at 3-5.

[0073] During the film formation process of step S5.4, the viscosity of the solution is adjusted to 100 cP-500 cP, and a layer-by-layer casting method is used to form a multi-layer composite diaphragm, in which the thickness of each layer is controlled to be 20 μm-80 μm.

[0074] The modified SiO 2 The contact angle of the nanoparticles after surface modification is controlled to be greater than 90°.

[0075] Example 1: Basic modified SiO 2 Preparation of Nanoparticles and Nafion Composite Membrane

[0076] step:

[0077] S1.1. Prepare a silane coupling agent hydrolyzate: mix ethanol and deionized water in a volume ratio of 95:5, and add 0.1 M hydrochloric acid as a catalyst.

[0078] S1.2. Addition of n-octyltriethoxysilane: according to SiO 2 5% of the mass of the nanoparticles was added with n-octyltriethoxysilane at a rate of 5 mL / min, and stirred at 200 rpm for 1 hour at room temperature to generate silanol monomers.

[0079] S2.1、SiO 2 Nanoparticle dispersion: Take 3g SiO with a particle size of 20nm 2 The nanoparticles were added with 50 mL of ethanol solution and treated with ultrasound at a frequency of 40 kHz and a power of 400 W for 30 min.

[0080] S3、SiO 2 Modification reaction: Add the silanol monomer generated in step S1 dropwise to SiO 2 The suspension was stirred at 60 °C for 6 hours and the pH value was controlled at 4 to obtain hydrophobic modified SiO 2 Nanoparticles.

[0081] S4.1. Preparation of Nafion resin solution: Nafion resin and N,N-dimethylformamide were mixed in a mass ratio of 1:7, and stirred at 200° C. for 4 hours until the Nafion was completely dissolved.

[0082] S4.2、SiO 2 Addition and ultrasonic treatment: Modified SiO 2 The particles were added into Nafion solution at 3 wt %, and ultrasonic treatment was performed for 30 minutes using a frequency of 40 kHz and a power of 400 W.

[0083] S5.1. Adding fluorocarbon surfactant: Add 1 wt% fluorocarbon surfactant based on the total mass of the Nafion solution and stir at 40° C. for 2 hours.

[0084] S5.4, film casting: cast the composite solution evenly on a glass plate, and control the film thickness to be 100 μm.

[0085] S6. Drying: The cast film was dried at 80°C for 2 hours and then at 120°C for 10 hours.

[0086] Summary: Through the basic n-octyltriethoxysilane modification, SiO 2 The dispersibility in Nafion is improved, and the prepared composite membrane has good ionic conductivity and anti-permeability.

[0087] Example 2: Adding a double silane coupling agent for composite modification

[0088] step:

[0089] S1.1. Preparation of disilane coupling agent: n-octyltriethoxysilane and 3-aminopropyltriethoxysilane were mixed in a ratio of 7:3, added to a mixed solution of ethanol and deionized water in a volume ratio of 95:5, and 0.1 M hydrochloric acid was added.

[0090] S1.2, addition of n-octyl triethoxysilane and 3-aminopropyl triethoxysilane: Mix the silane coupling agents according to SiO 2 7% of the mass was added dropwise at a rate of 5 mL / min and stirred for 1 hour.

[0091] S2.1、SiO 2 Nanoparticle dispersion: Take 3g SiO with a particle size of 20nm 2 Nanoparticles were added with 50 mL of toluene solution and the ultrasonic treatment parameters were the same as those in Example 1.

[0092] S3、SiO 2 Modification reaction: Stir at 70°C for 6 hours, control the pH to 4, and obtain surface-modified SiO 2 .

[0093] S4.1. Preparation of Nafion resin solution: Nafion and N,N-dimethylformamide were mixed in a mass ratio of 1:6, and the stirring parameters were the same as those in Example 1.

[0094] S4.2、SiO 2 Addition and ultrasonic treatment: Add 4wt% of composite modified SiO 2 Nanoparticles, ultrasonic treatment parameters are the same as in Example 1.

[0095] S5.1. Adding fluorocarbon surfactant: adding 1.5 wt % fluorocarbon surfactant, with stirring parameters the same as in Example 1.

[0096] S5.4, film casting: the film thickness is controlled to be 120μm.

[0097] S6. Drying: The parameters of preliminary drying and high temperature drying are the same as those in Example 1.

[0098] Summary: By using double silane coupling agents (n-octyl and aminopropyl), SiO 2 The interface bonding strength with Nafion and the mechanical strength of the composite membrane are improved.

[0099] Example 3: Adding a pretreatment step for nanoparticles

[0100] step:

[0101] S2.1、SiO 2 Particle pretreatment: Take 3g SiO with a particle size of 20nm 2 The nanoparticles were dried at 100 °C for 3 h to remove surface moisture.

[0102] The remaining steps are the same as those in Example 2.

[0103] Summary: By increasing SiO 2 The particle pretreatment step further improves the surface activity and modification effect of the particles, and enhances the dispersibility of the particles and the ionic conductivity of the membrane.

[0104] Embodiment 4: Adding layer-by-layer casting process

[0105] step:

[0106] S5.4. Layer-by-layer casting: The composite solution is divided into three layers and cast layer by layer, each layer having a thickness of 50 μm, and each layer is dried at 70° C. for 1 hour to finally form a composite diaphragm with a multilayer structure.

[0107] The remaining steps are the same as those in Example 3.

[0108] Summary: By adopting the layer-by-layer casting method, the structure of the diaphragm is more stable, the interface bonding between the layers is tighter, and the pressure resistance and permeation barrier of the diaphragm are significantly improved.

[0109] Example 5: Controlling Viscosity Adjustment During Film Formation

[0110] step:

[0111] S5.4. Viscosity control: During the layer-by-layer casting process, the viscosity of the composite solution is controlled to be 300 cP, and the viscosity of each layer of the solution is kept stable through continuous stirring.

[0112] The remaining steps are the same as those in Example 4.

[0113] Summary: By adjusting the viscosity during the film-forming process, the uniformity and thickness consistency of each layer are ensured, and the multilayer composite film finally prepared has good uniformity and conductivity.

[0114] Summary:

[0115] From Example 1 to Example 5, the SiO 2 Surface modification, pretreatment, dispersibility during the composite process, and film-forming process of the multilayer structure. Each example is further optimized on the basis of the previous one, and the composite membrane finally prepared shows significant improvement in ionic conductivity, mechanical strength, permeation barrier, etc. This series of process improvements not only improves the performance of the membrane, but also enhances its application adaptability in liquid flow batteries.

[0116] Experimental design background and objectives:

[0117] The purpose of this experimental design is to evaluate the use of n-octyltriethoxysilane (OTSO) modified SiO 2 The performance advantages of flow battery membranes prepared by combining nanoparticles with fluorocarbon surfactants and Nafion resins. The experiment will cover proton conductivity, mechanical properties, thermal stability, electrochemical properties, electrolyte barrier properties, etc., combined with more parametric tests to evaluate its innovation and superiority in practical applications.

[0118] Experimental objectives:

[0119] Verification of SiO modified by n-octyltriethoxysilane 2 The nanoparticle process improves the dispersion of the diaphragm in the Nafion resin matrix, thereby improving the proton conductivity.

[0120] Evaluate the role of fluorocarbon surfactants in enhancing the electrolyte barrier and long-term electrochemical stability of separators.

[0121] Through mechanical, thermal, chemical and other tests, it is proved that the modified SiO 2 Nanoparticles significantly improve the overall performance of the diaphragm.

[0122] Experimental group design

[0123] Experimental group 1 (invention group): OTSO-modified SiO 2 Nanoparticles + fluorocarbon surfactants.

[0124] Control group 1: unmodified SiO 2 Nanoparticles.

[0125] Control group 2: Silane coupling agent A modified SiO 2 Nanoparticles.

[0126] Control group 3: unmodified SiO 2 + Fluorocarbon surfactant.

[0127] Control group 4: Prior art flow battery separator.

[0128] Experiment 1: Proton conductivity test

[0129] Purpose:

[0130] The proton conductivity of the composite membranes under different treatments was tested to evaluate the effect of OTSO modification on SiO 2 Dispersion of nanoparticles in Nafion matrix and its effect on proton conduction channels.

[0131] Experimental materials and equipment:

[0132] Materials: Nafion resin, n-octyltriethoxysilane (OTSO), silane coupling agent A, SiO 2 Nanoparticles (10nm-30nm), N,N-dimethylformamide (DMF), fluorocarbon surfactants.

[0133] Equipment: ultrasonic processor (frequency 40kHz, power 400W), electrochemical workstation (including AC impedance spectroscopy test function), spin coater.

[0134] Experimental steps:

[0135] SiO 2 Nanoparticle modification:

[0136] Experimental group 1: 2 g of SiO 2 Nanoparticles were added with 100 mL of ethanol solution and treated with ultrasound for 20 minutes. Under stirring at 60 °C, OTSO solution (OTSO to ethanol volume ratio of 10:90) was added dropwise to SiO 2 The suspension was stirred and reacted for 8 hours to form Si-O-Si bonds on its surface. After the modification was completed, it was washed and dried.

[0137] Control group 2: SiO was modified in the same way using commercially available silane coupling agent A. 2 Nanoparticles.

[0138] Control groups 1 and 3: using unmodified SiO 2 .

[0139] Nafion solution and modified SiO 2 complex:

[0140] Preparation of Nafion solution: Nafion resin was dissolved in DMF at a mass ratio of 1:7, stirred and dissolved for 6 hours, and kept at a constant temperature of 200°C.

[0141] Preparation of composite solution: SiO 2 The nanoparticles were added into Nafion solution at 2 wt % and ultrasonicated for 30 min.

[0142] Fluorocarbon surfactant addition:

[0143] Experimental group 1 and control group 3: 1 wt% of fluorocarbon surfactant was added and stirred evenly.

[0144] Diaphragm preparation:

[0145] The composite solution was evenly coated on a clean glass substrate with a film thickness of 100 μm, and the film was formed by a spin coater, with a preliminary drying temperature of 80°C for 2 hours and a high-temperature drying temperature of 120°C for 8 hours.

[0146] Proton conductivity test:

[0147] The proton conductivity of each group of diaphragms was tested using an electrochemical impedance spectroscopy (EIS) method, with a test frequency range of 1 Hz to 1 MHz. The test samples were placed in a constant temperature and humidity chamber at a relative humidity of 95% and a temperature of 25° C. for testing.

[0148] The proton conductivity was calculated by the following formula:

[0149]

[0150] Wherein, σ is the proton conductivity (S / cm), l is the membrane thickness, R is the impedance value, and A is the membrane area.

[0151] Table 1:

[0152]

[0153] Experimental analysis and discussion:

[0154] The proton conductivity of experimental group 1 was significantly higher than that of other control groups, which proved that OTSO modified SiO 2 Nanoparticles can effectively improve their dispersion in the Nafion matrix, thereby forming a more uniform and efficient proton conduction channel. 2 (Control group 1) Due to its agglomeration in Nafion, the proton conductivity was significantly reduced, while the use of only surfactant (Control group 3) failed to significantly improve the proton conductivity.

[0155] Experiment 2: Mechanical strength and elongation at break test

[0156] Purpose:

[0157] The mechanical properties of different separators, including tensile strength and elongation at break, were evaluated to verify the OTSO-modified SiO 2 Can it enhance SiO 2 The bonding strength between the membrane and the Nafion matrix is ​​improved, thereby improving the mechanical properties of the membrane.

[0158] Experimental materials and equipment

[0159] Materials: Same as Experiment 1.

[0160] Equipment: Electronic tensile testing machine, dumbbell sample cutting machine, thickness gauge.

[0161] Experimental procedures

[0162] Diaphragm preparation: Same as Experiment 1.

[0163] Sample preparation: Cut each group of diaphragms into standard dumbbell-shaped samples (ISO527 standard) with a thickness accurate to 100 μm.

[0164] Tensile test:

[0165] Mechanical testing was performed using an electronic tensile testing machine with a test speed set at 10 mm / min. The maximum tensile strength and elongation at break of the sample were recorded before fracture.

[0166] Calculate the elongation at break:

[0167]

[0168] Where ε is the elongation at break, and L is the length of the sample before and after stretching.

[0169] Table 2:

[0170]

[0171]

[0172] Experimental analysis and discussion:

[0173] The tensile strength and elongation at break of experimental group 1 were better than those of other control groups, indicating that SiO2 was modified by octyltriethoxysilane (OTSO). 2 After the nanoparticles were added, the interfacial bonding between the nanoparticles and the Nafion matrix was significantly enhanced. After OTSO modification, the nanoparticles were evenly dispersed and formed a close bond with the Nafion resin, thereby improving the mechanical strength and ductility of the composite membrane.

[0174] In contrast, unmodified SiO 2 The nanoparticles (control group 1) have poor dispersion in the Nafion matrix, resulting in lower tensile strength and ductility. Although the silane coupling agent A modification (control group 2) has improved, the performance is still inferior to that of OTSO modification.

[0175] Experiment 3: Electrolyte permeability test

[0176] Purpose:

[0177] Test membrane for vanadium ion VO 2+ The permeability of the electrolyte is used to evaluate the modified SiO 2 The effect of the combination of fluorocarbon surfactants on the barrier properties of membranes.

[0178] Experimental materials and equipment

[0179] Material: VOSO 4 solution and anhydrous magnesium sulfate solution, Nafion resin, OTSO, silane coupling agent A, SiO 2 Nanoparticles, fluorocarbon surfactants.

[0180] Equipment: U-type electrolytic cell apparatus, spectrophotometer, constant temperature oscillator.

[0181] Experimental steps:

[0182] Diaphragm preparation: Same as Experiment 1.

[0183] Test setup:

[0184] Install the prepared diaphragm in the middle of the U-shaped electrolytic cell, and place VOSO on the left and right sides. 4 solution and anhydrous magnesium sulfate solution.

[0185] Test method:

[0186] The electrolytic cell was placed on a thermostatic oscillator, the temperature was maintained at 25° C., and the oscillation speed was 100 rpm. Every hour, samples were taken from the left and right sides of the electrolytic cell, and the change in vanadium ion concentration was measured using a spectrophotometer.

[0187] The electrolyte permeability coefficient of the diaphragm is calculated by the formula:

[0188]

[0189] Where P is the permeability coefficient, 1 is the membrane thickness, t is the time, A is the membrane area, C 0 is the initial concentration, C t is the concentration at time t.

[0190] Table 3:

[0191]

[0192] Experimental analysis and discussion:

[0193] Experimental group 1 showed the best electrolyte barrier performance and the lowest electrolyte permeability, which was only 3.1×10 -8 cm 2 / s, penetration resistance up to 750Ω·cm 2 , which is much higher than that of other control groups. This indicates that OTSO-modified SiO 2 The synergistic effect of the fluorocarbon surfactant significantly improved the electrolyte barrier performance of the diaphragm. 2 The nanoparticles (control group 1) had the highest permeability and the lowest permeation resistance, indicating that they were unevenly dispersed in the Nafion matrix, making it difficult to form an effective barrier layer, and the electrolyte could easily pass through.

[0194] Experiment 4: Thermal stability test

[0195] Purpose:

[0196] The thermal decomposition temperature of the diaphragm under different treatment methods was tested by thermogravimetric analysis (TGA) to verify the OTSO-modified SiO 2 Improvement effect on thermal stability of the diaphragm.

[0197] Experimental materials and equipment:

[0198] Materials: Same as Experiment 1.

[0199] Equipment: Thermogravimetric analyzer (TGA), nitrogen protection system.

[0200] Experimental steps:

[0201] Diaphragm preparation: Same as Experiment 1.

[0202] Thermogravimetric analysis:

[0203] Each group of diaphragm samples was placed in a thermogravimetric analyzer and heated from 30°C to 600°C at a heating rate of 10°C / min under nitrogen protection. The mass loss curve of the sample versus temperature was recorded, and the thermal decomposition temperature and the final residual mass were analyzed.

[0204] Table 4:

[0205]

[0206] Experimental analysis and discussion:

[0207] Experimental group 1 showed the highest thermal decomposition temperature of 435 °C, which was much higher than that of the control group, indicating that OTSO modified SiO 2 It can significantly improve the thermal stability of the diaphragm. 2 The interface bonding with the Nafion matrix is ​​more stable, which effectively inhibits the thermal decomposition process of the membrane material. 2 The thermal decomposition temperature of is low, which means that it is more prone to decomposition under high temperature conditions and has insufficient thermal stability.

[0208] Experiment 5: Electrochemical stability test

[0209] Purpose:

[0210] The electrochemical stability and durability of each group of diaphragms in the actual working environment of the flow battery, especially under high current density conditions, were tested to verify the modified SiO 2 The effect of improving the electrochemical stability of the diaphragm.

[0211] Experimental materials and equipment

[0212] Materials: Vanadium ion electrolyte, Nafion resin, OTSO, silane coupling agent A, SiO 2 Nanoparticles, fluorocarbon surfactants.

[0213] Equipment: Experimental flow battery device, electrochemical workstation.

[0214] Experimental steps:

[0215] Diaphragm preparation: Same as Experiment 1.

[0216] Electrochemical testing:

[0217] The membrane was installed in the experimental flow battery. The battery electrolyte was vanadium ion solution and the current density was set to 160 mA / cm 2 Under constant current conditions, monitor the changes in battery voltage, work continuously for 24 hours, and record the voltage fluctuations.

[0218] The electrochemical stability and durability of each group of diaphragms were analyzed, and their performance changes during long-term operation were compared.

[0219] Table 5:

[0220]

[0221]

[0222] Experimental analysis and discussion

[0223] Experimental group 1 showed excellent electrochemical stability at 160 mA / cm 2 At a high current density of 1.5 Ω, the voltage fluctuation was only 45 mV after 24 hours of operation, and the continuous working time exceeded 24 hours. This shows that the SiO modified by OTSO 2 The synergistic effect of nanoparticles and fluorocarbon surfactants significantly improves the electrochemical stability of the separator. This stability is particularly important for the long-term operation of flow batteries, ensuring stable battery performance at high current density and reducing polarization and voltage fluctuations.

[0224] In contrast, unmodified SiO 2 The voltage fluctuation of (control group 1) is large, and the endurance time is only 8 hours, indicating that the unmodified SiO 2 The particles were not evenly dispersed in the Nafion matrix, resulting in poor electrochemical stability. 2 ) has improved, but still not as significant as the OTSO modification effect. The prior art diaphragm (control group 4) performed the worst, with large voltage fluctuations and short operating time, indicating that the durability of the conventional diaphragm at high current density is weak.

[0225] Experiment 6: Surface morphology and microstructure analysis

[0226] Purpose:

[0227] Scanning electron microscopy (SEM) was used to observe the surface morphology and cross-sectional microstructure of the diaphragm and evaluate the SiO 2 Dispersion of nanoparticles in Nafion matrix and interface bonding.

[0228] Experimental materials and equipment:

[0229] Materials: Diaphragm samples from the experimental and control groups.

[0230] Equipment: Scanning electron microscope (SEM), sample preparation equipment (microtome, conductive coater).

[0231] Experimental steps:

[0232] Sample preparation:

[0233] Each group of membrane samples was cut into a size suitable for SEM observation and subjected to freeze-fracture treatment to observe the cross-sectional structure of the membrane.

[0234] The samples were gold-plated using a conductive coating machine to increase the conductivity of the samples for easier SEM observation.

[0235] SEM observation:

[0236] The surface morphology and cross-sectional structure of each group of diaphragms were observed using a scanning electron microscope, with a focus on analyzing the SiO 2 Dispersion and interface bonding of nanoparticles in Nafion matrix.

[0237] Table 6:

[0238]

[0239] Experimental analysis and discussion:

[0240] Through SEM observation, it can be clearly seen that the SiO 2 The nanoparticles are very evenly distributed in the Nafion matrix, with almost no agglomeration. This indicates that OTSO modification significantly improves the dispersion of the nanoparticles in the matrix and effectively enhances the interfacial bonding between the particles and the Nafion matrix by forming stable Si-O-Si bonds. This tight bonding helps improve the mechanical properties and electrochemical stability of the separator.

[0241] Unmodified SiO 2The particles (control group 1) agglomerated severely in the matrix, resulting in poor interface bonding, which is consistent with the performance results of the previous test, indicating that the uneven dispersion of nanoparticles in the matrix is ​​the main reason for the poor performance of the diaphragm. Silane coupling agent A modification (control group 2) and the use of surfactants (control group 3) help improve the SiO 2 The dispersibility of the modified PTFE is better than that of OTSO.

[0242] Experimental summary and discussion:

[0243] Based on the experimental results, the present invention uses n-octyltriethoxysilane (OTSO) to modify SiO 2 The flow battery membrane prepared by nanoparticles and fluorocarbon surfactant composites shows significant advantages in various properties:

[0244] Proton conductivity: The proton conductivity of experimental group 1 is as high as 0.19S / cm, which is significantly higher than that of other control groups, indicating that OTSO modified SiO 2 It can effectively form a uniform proton conduction channel and improve proton conductivity.

[0245] Mechanical strength and elongation at break: The tensile strength of experimental group 1 was 36 MPa and the elongation at break was 145%, showing excellent mechanical properties. After OTSO modification, the nanoparticles were more closely integrated with the Nafion matrix, significantly enhancing the mechanical properties of the diaphragm.

[0246] Electrolyte barrier property: Experimental group 1 has the lowest electrolyte permeability and the highest permeation resistance, showing the strongest electrolyte barrier performance. This shows that through OTSO modification, the membrane's permeation resistance to electrolyte is significantly enhanced, reducing the risk of cross-contamination of electrolyte.

[0247] Thermal stability: The thermal decomposition temperature of experimental group 1 is as high as 435°C, which proves its excellent stability under high temperature conditions.

[0248] Electrochemical stability: After running at high current density for 24 hours, the voltage fluctuation of experimental group 1 was only 45mV, showing extremely high electrochemical stability and suitable for long-term operation of liquid flow batteries.

[0249] Microstructure analysis: SEM images show that SiO 2 The nanoparticles are evenly distributed in the Nafion matrix, with no obvious agglomeration and tight interface bonding. This structural characteristic is an important reason for the performance improvement.

[0250] Summarize:

[0251] The technical solution of the present invention adopts OTSO to modify SiO 2Nanoparticles not only significantly improve the proton conductivity and mechanical strength of the diaphragm in the flow battery, but also improve the thermal stability and electrolyte barrier performance of the diaphragm. Compared with the existing technology and other conventional modification methods, the present invention shows more significant performance advantages and is particularly suitable for application scenarios such as flow batteries that require high electrochemical stability and long life. These experimental results fully demonstrate the innovation and superiority of the present invention.

[0252] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A process for preparing a flow battery diaphragm by modifying SiO2, characterized in that: The following steps are involved: S1, preparing a silane coupling agent hydrolyzate, dissolving n-octyltriethoxysilane in a mixed solution of ethanol and deionized water, and stirring under acidic conditions to generate a silanol monomer; S2, dispersing SiO2 nanoparticles in ethanol or toluene, and dispersing by ultrasonic to form a uniform SiO2 suspension; S3, adding the silanol monomer in step S1 dropwise into the SiO2 suspension, stirring the reaction, so that the silanol reacts with the surface of the SiO2 particles to form Si-O-Si bonds, and the flexible chain polymer is grafted onto the surface of the nano-rigid SiO2 particles; S4, adding the modified SiO2 particles into the Nafion resin solution and dispersing them uniformly by ultrasonic treatment; S5, adding fluorocarbon surfactant, stirring evenly and casting into a film; S6. Preliminary drying is performed at 70°C-80°C, and then further drying is performed at a high temperature of 120°C-140°C to prepare a modified SiO2 and Nafion composite liquid flow battery membrane.

2. The process for preparing a flow battery diaphragm by modified SiO2 according to claim 1, characterized in that: The S1 step specifically includes the following steps: S1.

1. Preparation of solvent and catalyst: Ethanol and deionized water are mixed in a volume ratio of 90:10 to 98:2 as a dissolving agent; Add 0.05M to 0.2M hydrochloric acid as a catalyst to the mixed solvent; S1.2, addition of n-octyltriethoxysilane: The amount of n-octyltriethoxysilane added is 2%-10% of the mass of SiO2 particles; n-Octyltriethoxysilane is added dropwise to the solution at a rate of 1 mL / min-10 mL / min, and stirred at room temperature with a stirring speed of 100 rpm-300 rpm and a reaction time of 0.5-2 h.

3. The process for preparing a flow battery diaphragm by modified SiO2 according to claim 1, characterized in that: The S2 step specifically includes the following steps: S2.

1. Add 1g-5g of SiO2 nanoparticles with a particle size of 10nm-30nm into ethanol or toluene solution, and the solvent volume is 30mL-100mL; S2.

2. Ultrasonic dispersion is performed for 10 min to 60 min using an ultrasonic processor with a frequency of 20 kHz to 60 kHz and a power of 200 W to 600 W to obtain a uniformly dispersed SiO2 suspension.

4. The process for preparing a flow battery diaphragm by modified SiO2 according to claim 1, characterized in that: In the step S3, the stirring temperature is 40°C-80°C, and the stirring time is 4h-8h.

5. The process for preparing a flow battery diaphragm by modified SiO2 according to claim 1, characterized in that: The S4 step specifically includes the following steps: S4.1, preparation of Nafion resin solution: Nafion resin and N,N-dimethylformamide are mixed in a mass ratio of 1:5-1:10, and stirred at 180°C-240°C for 2h-6h until the Nafion resin is completely dissolved; S4.2, adding modified SiO2 nanoparticles: adding modified SiO2 nanoparticles into Nafion solution at a ratio of 1wt%-3wt%; S4.

3. Ultrasonic treatment: Use an ultrasonic processor to treat the mixed solution prepared in step S4.2, with an ultrasonic frequency of 20kHz-60kHz, a power of 200W-500W, and a treatment time of 10min-60min.

6. The process for preparing a flow battery diaphragm by modified SiO2 according to claim 1, characterized in that: The step S5 specifically includes the following steps: S5.

1. Addition of fluorocarbon surfactant: the amount of fluorocarbon surfactant added is 0.5wt%-2wt% of the total mass of Nafion solution; S5.2, stirring conditions: stirring at a temperature of 20°C-60°C for 1h-3h, and a stirring speed of 100rpm-400rpm; S5.3, ultrasonic stirring: place the solution in an ultrasonic bath, the ultrasonic time is 10min-60min, and the ultrasonic frequency is 20kHz-40kHz; S5.

4. Film casting: Cast the composite solution evenly on a clean glass plate.

7. The process for preparing a flow battery diaphragm by modified SiO2 according to claim 1, characterized in that: In the step S6, the initial drying rate is 0.1°C / min-0.5°C / min, and the high temperature drying rate is 0.2°C / min-1°C / min, so as to control the porosity of the membrane to be 20%-40%.

8. The process for preparing a flow battery diaphragm by modified SiO2 according to claim 1, characterized in that: The pH value of the SiO2 suspension in the S3 step is controlled at 3-5.

9. The process for preparing a flow battery diaphragm by modified SiO2 according to claim 1, characterized in that: During the film forming process of step S5.4, the viscosity of the solution is adjusted to 100 cP-500 cP, and a layer-by-layer casting method is used to form a multi-layer composite diaphragm, wherein the thickness of each layer is controlled to be 20 μm-80 μm.

10. The process for preparing a flow battery diaphragm by modified SiO2 according to claim 1, characterized in that: The contact angle of the modified SiO2 nanoparticles in step S4 is controlled to be greater than 90° after the surface modification.